2019
DOI: 10.1021/acs.est.9b01517
|View full text |Cite|
|
Sign up to set email alerts
|

Human Consumption of Microplastics

Abstract: Microplastics are ubiquitous across ecosystems, yet the exposure risk to humans is unresolved. Focusing on the American diet, we evaluated the number of microplastic particles in commonly consumed foods in relation to their recommended daily intake. The potential for microplastic inhalation and how the source of drinking water may affect microplastic consumption were also explored. Our analysis used 402 data points from 26 studies, which represents over 3600 processed samples. Evaluating approximately 15% of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
740
1
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,568 publications
(906 citation statements)
references
References 23 publications
10
740
1
23
Order By: Relevance
“…Although these figures are subject to a large range of variation, it is thought that they probably underestimate the total ingested microplastic load; however, any consequent health effects are presently unknown. 76 Definitive evidence that microplastics are getting into human bodies is provided by their presence in human stools, although the study was small, with only eight volunteers being sampled from Europe, Japan and Russia. 77 However, the matter of whether the ingestion of microplastics is harmful to humans remains largely unresolved, and for example, in an EU Report, it is concluded that there is no hard evidence for harmful effects on humans or the environment, except in small pockets, 78 while another EU report emphasises the need to obtain better evidence on which to base policy regarding microplastics.…”
Section: Environmental and Human Health Effects Of Plastic Pollutionmentioning
confidence: 99%
“…Although these figures are subject to a large range of variation, it is thought that they probably underestimate the total ingested microplastic load; however, any consequent health effects are presently unknown. 76 Definitive evidence that microplastics are getting into human bodies is provided by their presence in human stools, although the study was small, with only eight volunteers being sampled from Europe, Japan and Russia. 77 However, the matter of whether the ingestion of microplastics is harmful to humans remains largely unresolved, and for example, in an EU Report, it is concluded that there is no hard evidence for harmful effects on humans or the environment, except in small pockets, 78 while another EU report emphasises the need to obtain better evidence on which to base policy regarding microplastics.…”
Section: Environmental and Human Health Effects Of Plastic Pollutionmentioning
confidence: 99%
“…While plastics can provide benefits such as prolonging the lifetime of food products, and thereby indirectly contribute to water and fuel use reductions, the vast majority of single use plastics are not effectively recycled, and ultimately may contaminate the environment. A recent study found that an average American consumes 39000–52000 microplastic particles of plastic per year …”
Section: Where Will the Field Of Macromolecules Go Over The Next 20–3mentioning
confidence: 99%
“…A recent study found that an average American consumes 39000-52000 microplastic particles of plastic per year. [126] These recent challenges offer new opportunities for the field. Companies are commercializing new processes for polymer recycling and new products based on recycled polymers.…”
Section: Does the Field Of Macromolecules Encompass Service Tools Or mentioning
confidence: 99%
“…These ubiquitous environmental contaminants have recently been featured in the media, making national headlines after a study estimated that adults consume tens of thousands of marine microplastics each year (Cox et al 2019). Despite the attention, current scientifi c consensus suggests that there are few to no known human health risks associated with the consumption of microplastics.…”
Section: A Call To Include Indirect Effects Of Marine Microplastics Imentioning
confidence: 99%